The Effect of Suction Endotracheal Tube on Oxygen Saturation of Respiratory Failure Patients - Chicilia Puspita; Akhmad Rifai; Addi Mardi Harnanto; Sugiyarto Sugiyarto (Universitas Islam Jember, 2022)
Respiratory failure can be characterized by a decrease in oxygen saturation. Oxygen saturation is the percentage of hemoglobin about oxygen in the arteries. Normal oxygen saturation is in the range of 95% - 100%. The cause of respiratory failure can occur due to pulmonary disorders such as pneumonia, sepsis, heart failure, or neurological disorders. Airway obstruction is a condition in which a person is unable to expel secretions effectively, this condition can lead to respiratory failure. Suction aims to free the airway, reduce the buildup of secretions, and prevent lung infections. This literature review is to determine the effect of endotracheal tube suction on the oxygen saturation of patients with respiratory failure. Search from scientific publications or research journals related to the effect of endotracheal tube suction on the oxygen saturation of patients with respiratory failure. Each scientific publication or research journal has been selected based on inclusion criteria. The results of the nine articles or journals analyzed showed that there was an effect of endotracheal tube suction on the oxygen saturation of patients with respiratory failure as indicated by the p-value <0.05. There is an effect of endotracheal tube suction on the oxygen saturation of patients with respiratory failure.